The Correlation Between Arterial and Venous Diameters in Chronic Kidney Failure Patients and the Success of Functional Maturation of the Brachiocephalic AV Fistula in Patients with and Without Diabetes Mellitus - Josep Joko Hendratno; Raden Suhartono; Nani Cahyani (Eduvest - Journal of Universal Studies, 2026)
Various factors influence the success of arteriovenous fistula (AVF) creation, including vascular anatomical conditions, intraoperative hemodynamics, comorbidities, and arterial and venous diameters. In patients with diabetes mellitus (DM), vascular changes such as venous intimal hyperplasia and arterial atherosclerosis play a crucial role in determining AVF functional maturity. This study aims to analyze the correlation between arterial and venous diameters and the success of AVF functional maturity in patients with chronic kidney failure, both with and without diabetes mellitus. This study employed a retrospective cohort design conducted at the vascular surgery department of RSCM, with data collected retrospectively from 2022 to 2025. Data analysis began with normality testing using the Kolmogorov-Smirnov or Shapiro-Wilk test. Descriptive statistics were used to present demographic and clinical characteristics. Bivariate analysis was performed using Pearson or Spearman correlation tests depending on data distribution. Arterial and venous diameters significantly influenced AVF functional maturity (p < 0.05). Patients with mature AVFs had larger arterial diameters (median 3.8 mm) compared to immature AVFs (3.5 mm), and significantly larger venous diameters (2.8 mm vs 2.15 mm). In DM patients, arterial diameter did not significantly affect AVF maturity (p > 0.05), whereas venous diameter showed a significant effect (p < 0.05). A strong negative correlation was observed between vein diameter and immature AVF incidence (r = -0.708; p < 0.05).  Venous diameter is a significant determinant of AVF functional maturity, particularly in patients with diabetes mellitus, while arterial diameter shows limited influence in this group.